Development of a superconducting-phase-transition thermometer (SPT) for the application in a time-of-flight mass spectrometer (TOF-MS) for heavy-mass molecules; Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment; Vol. 520, iss. 1-3 - Rutzinger S.; Christ P.; Probst F.; Seidel W.; Uchaykin S. V. Sergey Victorovich; Stark M. (2004, 2004)
Title screen